PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN PEMBELAJARAN KONTEKSTUAL DI SEKOLAH DASAR - Astriani, Merri; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve students’ ability on writing a description using contextual learning toward fourth grade students of SDN 03 Suti Semarang. The form of this research is classroom action research with description as the method. In this research, the researcher just portrayed of what has happened towards the objects and the area of this research. The data collection used in this reseach is IPKG I, IPKG II, and students’ observation sheets. In the first cycle, the average of students’ evaluation is 76.19 with 16 students passed the test. In the second cycle, the students’evaluation becomes 85.71 with 18 students passed the test. In the third cycle, the average students’ evaluation improves to 90.48 with 19 students passed the test. By those results, it can be concluded that Bahasa Indonesia learning using contextual learning can improve students’ability on writing on a description. Keywords: Improving, Writing a Description, Contextual Learnin